PAC1 Receptor Mediates Electroacupuncture-Induced Neuro and Immune Protection During Cisplatin Chemotherapy - Li, Shanshan; Huang, Jin; Guo, Yi; Wang, Jiaqi; Lu, Shanshan; Wang, Bin; Gong, Yinan; Qin, Siru; Zhao, Suhong; Wang, Shenjun; Liu, Yangyang; Fang, Yuxin; et al. (Frontiers in Immunology, 2021)
Platinum-based chemotherapy is an effective treatment used in multiple tumor treatments, but produces severe side effects including neurotoxicity, anemia, and immunosuppression, which limits its anti-tumor efficacy and increases the risk of infections. Electroacupuncture (EA) is often used to ameliorate these side effects, but its mechanism is unknown. Here, we report that EA on ST36 and SP6 prevents cisplatin-induced neurotoxicity and immunosuppression. EA induces neuroprotection, prevents pain-related neurotoxicity, preserves bone marrow (BM) hematopoiesis, and peripheral levels of leukocytes. EA activates sympathetic BM terminals to release pituitary adenylate cyclase activating polypeptide (PACAP). PACAP-receptor PAC1-antagonists abrogate the effects of EA, whereas PAC1-agonists mimic EA, prevent neurotoxicity, immunosuppression, and preserve BM hematopoiesis during cisplatin chemotherapy. Our results indicate that PAC1-agonists may provide therapeutic advantages during chemotherapy to treat patients with advanced neurotoxicity or neuropathies limiting EA efficacy.